Thermal emission, shock modification, and X-ray emitting ejecta in SN 1006 - Miceli, M. (2009)
Context: Efficient particle acceleration can modify the structure of supernova remnants. We present the results of a combined analysis of the XMM-Newton EPIC archive observations of SN 1006. Aims: We attempt to describe the spatial distribution of the physical and chemical properties of the X-ray emitting plasma at the shock front. We investigate the contribution of thermal and non-thermal emission to the X-ray spectrum at the rim of the remnant to study how the acceleration processes affect the X-ray emitting plasma. Methods: We perform a spatially resolved spectral analysis of a set of regions covering the entire rim of the shell and we apply our results in producing a count-rate image of the ?pure? thermal emission of SN 1006 in the 0.5-0.8 keV energy band (subtracting the non-thermal contribution). This image differs significantly from the total image in the same band, especially close to the bright limbs. Results: We find that thermal X-ray emission can be associated with the ejecta and study the azimuthal variation in the physical and chemical properties of the ejecta by identifying anisotropies in the temperature and chemical composition. By employing our thermal image, we trace the position of the contact discontinuity over the entire shell and compare it with that expected from 3D MHD models of SNRs with an unmodified shock. Conclusions: We conclude that the shock is modified everywhere in the rim and that the aspect angle between the interstellar magnetic field and the line of sight is significantly lower than 90°.